(untitled) - Rossano, Matthew J. (Hoboken, NJ., 2003)
Written in a lively and engaging manner, this new work places evolutionary psychology within the broad sweep of our primate heritage and the full scope of our evolutionary story. Beginning with the basics of evolution, the book first unpacks the far-ranging saga of human evolution, then moves on to examine motor behavior and emotions, sexual behavior and mate selection, and higher cognition.
Keywords: Religion,Human evolution,Tôn giáo,Giá trị con người; Religious aspects,Khía cạnh tôn giáo